Omani short version of organizational health inventory: Application of item response theory - Aieman Ahmad Al-Omari, Yousef Abdelqader Abu Shindi,; Alabri, Khalaf Marhoun (Opción, 2020)
The current study used item response theory (IRT) to analyze data from (N=323) Omani teachers randomly selected participated in this study to investigate whether a subset of items could be selected to create a short version of the instrument. As a result, the high correlation coefficients between the examinee ability parameter estimated on the easy and difficult test items and did not change between the two versions. This is an indication of the improvement of the unchanging ability estimated invariant. In conclusion, the study concluded a short version of the OHI scale. It contains 30 items distributed on seven Domains